Distribution of some neophytes in the Kyiv (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
New localities of alien plant species Thladiantha dubia Bunge, Robinia viscosa Vent., Galinsoga urticifolia (Kunth) Benth., Heracleum mantegazzianum Sommier & Levier, Rumex triangulivalvis (Danser) Rech., Euphorbia dentata Michx., Tribulus terrestris L.are reported in the Kyiv.
Keywords: alien plants, distribution, Kyiv.